Relationship Between Female Reproductive Factors and Osteoporosis among Postmenopausal Women in Malaysia: A Systematic Review and Meta-Analysis of Observational Studies - Mohamed, Siti Zulfarina; Nordin, Siti Hawa; Ashikin Taib, Mai Nurul; Sharifudin, Mohd Ariff (IIUM Medical Journal Malaysia, 2025)
Numerous studies in Malaysia have investigated the potential link between female reproductive factors and osteoporosis in postmenopausal women; however, a comprehensive synthesis of these findings is lacking. This systematic review seeks to elucidate the association between female reproductive factors and bone health indices in postmenopausal Malaysian women. A comprehensive search of PubMed, Scopus, and the Cochrane Library databases was conducted up to October 2024. Inclusion criteria comprised case-control and cross-sectional studies that reported comparisons, correlations, or regression analyses involving years-since-menopause, parity, or lactation with osteoporosis. Qualitative analysis was conducted on eight cross-sectional studies and one case-control study. Five out of the nine studies indicated a relationship between years-since-menopause and osteoporosis. Additionally, two out of four studies found a relationship between parity and osteoporosis, while two out of three studies demonstrated a relationship between lactation and osteoporosis. Quantitatively, a meta-analysis was performed for five studies, with a pooled sample size of 1134 postmenopausal women. A significant negative correlation emerged between years-since-menopause and osteoporosis indices (Fisher’s correlation coefficient: -2.51 [95% CI-0.305-0.195], p<0.001, fixed-effect model, I2 97%). Unfortunately, the available data on parity and lactation history were insufficient for meta-analysis of correlation. Limitations in the regression data did not allow for meta-analysis. The findings underscore the potential importance of years-since-menopause as a reproductive factor associated with osteoporosis in postmenopausal Malaysian women. Additional research is imperative to substantiate this association and contribute to the development of a robust risk assessment tool.